Food Security Status in Bangladesh: An Analytical Overview (Global Journal of Human-Social Science, 2016)
Food is a basic human need for human survival To achieve Millennium Development Goals food security has become top most concern for Bangladesh This paper examines performance challenges and policies in food security in terms of availability access and absorption or nutrition Specifically this paper focuses on the progress in supply side of food in terms of availability at the national level and how far has Bangladesh progressed in attaining access to food and nutrition requirements at the household level The paper argues in favor of strengthening the role of various social safety net programs increasing subsidy in agriculture sector and enhancing purchasing power of the people food security production and availability of food grains This paper has also given attention on the effect of inflation on price of food grains The paper concludes that Bangladesh should target self-sufficiency in food grains production to satisfy domestic demand in normal production years
Keywords: availability; access; and absorption or nutrition